Rotational Rebound Attacks on Reduced Skein - Khovratovich, Dmitry; Nikolić, Ivica; Rechberger, Christian (Journal of cryptology, 2014)
In this paper we combine two powerful methods of symmetric cryptanalysis: rotational cryptanalysis and the rebound attack. Rotational cryptanalysis was designed for the analysis of bit-oriented designs like ARX (Addition-Rotation-XOR) schemes. It has been applied to several hash functions and block ciphers, including the new standard SHA-3 (Keccak). The rebound attack is a start-from-the-middle approach for finding differential paths and conforming pairs in byte-oriented designs like Substitution-Permutation networks and AES. We apply our new compositional attack to the reduced version of the hash function Skein, a finalist of the SHA-3 competition. Our attack penetrates more than two thirds of the Skein core—the cipher Threefish, and made the designers to change the submission in order to prevent it. The rebound part of our attack has been significantly enhanced to deliver results on the largest number of rounds. We also use neutral bits and message modification methods from the practice of collision search in MD5 and SHA-1 hash functions. These methods push the rotational property through more rounds than previous analysis suggested, and eventually establish a distinguishing property for the reduced Threefish cipher. We formally prove that such a property cannot be found for an ideal cipher within the complexity limits of our attack. The complexity estimates are supported by extensive experiments.